(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: The objective of this study was to compare the pain relief effectiveness of PIEB using a mixture of Anaropin 0.08% and Fentanyl 1 mcg/ml compared to Anaropin 0.1% and Fentanyl 1 mcg/ml in epidural anesthesia during labor. Subjects and methods: A randomized clinical trial was used in this study. A simple random sampling method was used to recruit 83 pregnant women and divided them into two groups, group 1 Anaropin 0.1% and Fentanyl 1 mcg/ml and group 2 using Anaropin 0.08% and Fentanyl 1 mcg/ml. Results: There was almost no difference in VAS scores between the groups using Anaropin 0.1% and Anaropin 0.08%. At the stage of full cervical dilation and the II stage, the VAS score of the group using Anaropin 0.08% was higher than that of the group using Anaropin 0.1%. The satisfaction level of the group using Anaropin 0.08% was higher than that of the group using Anaropin 0.1%. Conclusion: Anaropin 0.08% had similar pain relief effectiveness but lower drug dosage, lower incidence of adverse effects and higher satisfaction compared to Anaropin 0.1%.